Effect of seated/biped opponents and differences between experienced and novice wheelchair tennis players - Reina Vaillo, R.; Moreno Hernandez, F. J.; Sanz Rivas, D.; del Campo, V. L. (Medicine and Science in Tennis, 2004)
The aims of our study were: a) to study the visual and motor responses of tennis and wheelchair tennis players in the return to serve against biped and wheeler opponents; b) to study the differences between experienced and novice wheelchair tennis player. The study has been undertaken from a perception-action perspective, where action is continuously being coupled to the perceptual information presented (14,15). The higher visual fixation scores on the ball in the serves performed by seated opponents could be due to the fact that the player grabs the rim of the wheelchair with the free arm, in order to obtain stability during the serve. The results obtained for the free-arm and the ball in the phase A, with higher mean values among biped servers, could support this explanation. Nevertheless, it could also be due to the lesser mobility experienced by the players seated in the wheelchair, and the need to acquire information from different locations of the biped server. Therefore, against seated opponents, the players perform a longer pursuit of the ball's trajectory and they show lower fixations on the area where the racket hits the ball. Furthermore, they employ less time in starting the pursuit of the ball's trajectory because the serves of those opponents was slower than those of biped servers. This explanation is supported by higher fixations on advanced areas of the flight ball's position for the serves performed by seated players. On the other hand, higher fixations were obtained in the posterior area of the flight ball's position for the serves performed by biped opponents. The higher values in the reaction response against biped opponents could be due to a greater movement´ width, and it would offer important cues to help in predicting trajectory before the serve than it would be the case with seated servers (13).